Effectiveness of an educational program to promote changes in the knowledges attitudes and practices of the teens on its vih/aids, in the educational institution Illathupa - Huánuco 2006-2007 - Manrique de Lara Suarez, Digna (2009)
The aim of this study was to determine the effectiveness of an educational program to promote changes in knowledge, attitudes and practices of adolescents about sexually transmitted diseases (STIs, HIV / AIDS) in the national school Illathupa Huánuco 2006-2007. Was applied pre and post test using a structured questionnaire with questions that allowed the balancing of both groups on Knowledge, Attitude and Practice of (STIs, HIV / AIDS). The sample consisted of 116 adolescent students of the 4th year of secondary education, 66 for the experimental group and 50 in the control group. After the implementation of the educational program between the two groups was an increase in the level of knowledge related to forms of transmission, prevention and treatment, statistically significant differences (Chi = 9.22). In the experimental group showed a significant difference in knowledge (Chi = 5.83). On attitudes related to rejection or abandonment of an infected person, preventing the use of condoms, delaying sexual intercourse.